Private Security Sector in Quest for Legitimacy and Public Trust (Annual of the Faculty of Philosophy in Skopje, 2017)
The purpose of this chapter is to question the degree and the nature of legitimacy held by the private security sector, and how this can affect the role private actors play in the field of policing and in the governance of security. We draw mainly on the existing academic literature on private policing, as well as our own qualitative research conducted in Macedonia. If private security personnel have less legitimacy (and force) than their public counterpart (state police), one should keep in mind two nuances: first, there is a tendency toward shrinking of the gap between the two sectors; and second, as private security officers and companies are likely to become increasingly involved in traditional police functions, their lack of legitimacy and legal powers could significantly impede their actions in the future. However, at this point the legitimacy shortcomings of private security in Macedonia do not represent a visible problem, considering that the private security actors are usually given specific legal powers and they do not rely on legitimacy as much as the police do in order to do their job.
Keywords: PRIVATE SECURITY; PUBLIC TRUST; LEGITIMACY; GOVERNANCE OF SECURITY; MEDIA